1995
DOI: 10.1128/aem.61.12.4436-4440.1995
|View full text |Cite
|
Sign up to set email alerts
|

Natural assemblages of marine bacteria exhibiting high-speed motility and large accelerations

Abstract: Natural communities of marine bacteria, an isolate (FMB-Bf3) from one marine community, and Escherichia coli were examined by video microscopy for the magnitude and uniformity of their speed. Natural communities formed tight microswarms that showed higher speeds (mean ‫؍‬ 230 m s ؊1) than did E. coli (15 m s ؊1) or FMB-Bf3 (mean ‫؍‬ 62 m s ؊1). Outside the microswarms, the marine bacteria slowed to 45 m s ؊1. Between turns, in mid run, and while travelling in straight lines, the natural-community bacteria acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 24 publications
4
21
0
Order By: Relevance
“…A prediction that follows from the variation range hypothesis is that when collective speeds are five times maximal individual speeds, as indicated by Mitchell et al (1995), some bacteria among the collective will be smaller in size or maximal metabolic capacity than their larger or stronger counterparts by a corresponding factor of five, bearing in mind appropriate adjustments for the unique fluid dynamics of bacteria, as discussed.…”
Section: Consistent With the Variation Range Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…A prediction that follows from the variation range hypothesis is that when collective speeds are five times maximal individual speeds, as indicated by Mitchell et al (1995), some bacteria among the collective will be smaller in size or maximal metabolic capacity than their larger or stronger counterparts by a corresponding factor of five, bearing in mind appropriate adjustments for the unique fluid dynamics of bacteria, as discussed.…”
Section: Consistent With the Variation Range Hypothesismentioning
confidence: 99%
“…Indeed, Mitchell et al (1995) identified the unresolved extraordinary efficiencies in energy consumption by which micro-swarming bacteria move in speeds at multiples of the predicted 100 % energetic consumption. These efficiencies imply a set of energy saving mechanisms that are not yet well understood.…”
Section: High Collective Bacteria Speed Compared To Speed In Isolationmentioning
confidence: 99%
“…A related consideration is variation in swimming speeds across individuals. Several studies have noted the highly heterogeneous nature of bacterial populations in terms of swimming speeds [7,39,40]. In our models, we fixed the swimming speed; an obvious extension is to replace this with a fluctuating quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the difference between swimming and non-swimming cells is not clear, previous studies have reported a few mechanisms of motility regulation in bacteria. Motility in some species is regulated by environmental conditions [42][43][44], and the production of flagella can be regulated by a genetic switch [45]. Non-swimming cells were not stuck to chamber surfaces, as all cells migrated multiple cell lengths during the data acquisition period.…”
Section: Band Speed Is Not Correlated With Any Individual Strain Propmentioning
confidence: 99%
“…Although non-swimming cells would contribute to the shape and dynamics of chemotactic gradients, it seems reasonable that non-swimming cells would not strongly influence the band speed. Many studies have shown that fraction of motile bacterial cells is usually low (about 10%) in natural environment, and may vary a lot (5% to 70%) depending on environmental factors [12,42,44,46,47].…”
Section: Band Speed Is Not Correlated With Any Individual Strain Propmentioning
confidence: 99%